Bacterial and fungal bioburden reduction on material surfaces using various sterilization techniques suitable for spacecraft decontamination - Kimura, Shunta; Ishikawa, Shu; Hayashi, Nobuya; Fujita, Kazuhisa; Inatomi, Yuko; Suzuki, Shino (Frontiers in Microbiology, 2023)
Planetary protection is a guiding principle aiming to prevent microbial contamination of the solar system by spacecraft (forward contamination) and extraterrestrial contamination of the Earth (backward contamination). Bioburden reduction on spacecraft, including cruise and landing systems, is required to prevent microbial contamination from Earth during space exploration missions. Several sterilization methods are available; however, selecting appropriate methods is essential to eliminate a broad spectrum of microorganisms without damaging spacecraft components during manufacturing and assembly. Here, we compared the effects of different bioburden reduction techniques, including dry heat, ultraviolet (UV) light, isopropyl alcohol (IPA), hydrogen peroxide (H2O2), vaporized hydrogen peroxide (VHP), and oxygen and argon plasma on microorganisms with different resistance capacities. These microorganisms included Bacillus atrophaeus spores and Aspergillus niger spores, Deinococcus radiodurans, and Brevundimonas diminuta, all important microorganisms for considering planetary protection. B. atrophaeus spores showed the highest resistance to dry heat but could be reliably sterilized (i.e., under detection limit) through extended time or increased temperature. A. niger spores and D. radiodurans were highly resistant to UV light. Seventy percent of IPA and 7.5% of H2O2 treatments effectively sterilized D. radiodurans and B. diminuta but showed no immediate bactericidal effect against B. atrophaeus spores. IPA immediately sterilized A. niger spores, but H2O2 did not. During VHP treatment under reduced pressure, viable B. atrophaeus spores and A. niger spores were quickly reduced by approximately two log orders. Oxygen plasma sterilized D. radiodurans but did not eliminate B. atrophaeus spores. In contrast, argon plasma sterilized B. atrophaeus but not D. radiodurans. Therefore, dry heat could be used for heat-resistant component bioburden reduction, and VHP or plasma for non-heat-resistant components in bulk bioburden reduction. Furthermore, IPA, H2O2, or UV could be used for additional surface bioburden reduction during assembly and testing. The systemic comparison of sterilization efficiencies under identical experimental conditions in this study provides basic criteria for determining which sterilization techniques should be selected during bioburden reduction for forward planetary protection.